Impact of seasonal cycle on rheumatoid arthritis based on genetic and epigenetic mechanisms - E.K, Krishna Priya; P.R, Shidhi; S, Sreedevi; Banerjee, Moinak (Frontiers in Immunology, 2025)
Rheumatoid arthritis is an autoimmune disease characterized by chronic inflammation and progressive joint destruction. Genetic and environmental risk factors contribute to the development of rheumatoid arthritis (RA). Among environmental factors, seasonal cycles are reported to impact the clinical phenotypes in RA, with rheumatic flares being aggravated during the winter season. Gaining insight into the seasonal effects on molecular drivers can be vital in resolving seasonal cycles in RA pathogenesis. To understand this phenomenon, genome-wide association study (GWAS) and candidate genes were reviewed to identify their role in susceptibility to RA. Subsequently, it was verified how many of these genes are modulated by seasonal influences. Furthermore, the role of epigenetic modifications, such as DNA methylation and non-coding RNAs, involved in RA pathogenesis and whether these epigenetic effects are also impacted by seasonal fluctuation were examined. Finally, it was investigated how these genetic and epigenetic mechanisms result in the breakdown of self-tolerance and the initiation of an autoimmune action. Upon overlapping the genetic and epigenetic observations influenced by seasonal cycles, it was evident that seasonal cycles do impact the genetic and epigenetic machinery, which possibly can explain the reasons for seasonal flares in RA pathogenesis. The evidence indicates that genetic and epigenetic mechanisms are driven by climatic variation and that the timing and duration of the aberrant expression of immune response genes will drive the autoantibodies to develop seasonal flares of RA.